Biogenic synthesis, characterization, antibacterial and antioxidant activities of silver nanoparticles mediated from Tamarindus indica Linn fruit pulp extract - Kehinde Oluwakemi Fagbemi; Olufunmiso Olusola Olajuyigbe; Roger Coopoosamy (Shahrekord University of Medical Sciences, 2023)
Introduction: Due to the numerous potentials discovered from biologically synthesized silver nanoparticles (SNPs), the interest of many researchers has been stirred up. Tamarindus indica fruit has many therapeutic potentials attributed to fruit. Hence, the objective of this study was to synthesize, characterize, and evaluate the in vitro antioxidant and antibacterial activities of SNPs mediated from T. indica fruit pulp extract. Methods: The bioreduction of silver nitrate was performed using methanol extract of T. indica fruit pulp. UV-vis spectrophotometry studies at 480 nm confirmed the synthesis of SNPs. The synthesized nanoparticles were characterized using Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy-dispersive X-ray spectroscopy (EDX). The antioxidant properties were assessed using methods of ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH). The antibacterial potential was evaluated using the agar well technique. Results: FTIR spectroscopy revealed that the presence of various functional groups was responsible for reduction and stabilization during the biosynthesis process. With the aid of ImageJ software, the size of the nanoparticles was determined to be in the range of 18-50 nm. The anti-oxidation activity assays showed a strong reducing potential towards the radicals tested. Lastly, strong antibacterial activities were observed when the nanoparticles were tested on some pathogenic bacteria through the agar well method. Conclusion: This biological method of synthesizing SNP from T. indica has shown significant enhancement in its biological activities in terms of antibacterial and antioxidant properties; thus, it might be considered a therapeutic agent.